ETORO : Indigenous Botanical Knowledge Management System of Penans, 7-9 November 2013 - Universiti Malaysia Sarawak, ISITI-CoERI (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Winner at PECIPTA International Conference and Exposition On Invention of Institutions of Higher Learning